Cahiers du genre: « De la contraception à l’enfantement : l’offre technologique en question » - Béland, Bibiane (Recherches féministes, 2000)
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du sud; approches et analyses; brésil; corps; corps des femmes; cours; discipline; discours dominant; droits des femmes*; europe; france; maternité; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques

Sexing the body: Gender politics and the construction of sexuality - Fausto-Sterling, Anne (Basic Books, 2000)
Discusses the causes and determining factors of gender behavior differences and sexual identity, particularly biology and societal expectations, and argues that differences between male and female are not always distinct.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme matérialiste; genre; histoire et politique; hétérosexisme; injustices épistémiques; philosophie politique; premier cycle; production des savoirs; ressource en ligne; sciences humaines; sciences sociales; sex3383; sexe/genre; sexualité; sociologie; systèmes d'oppressions; thématiques; épistémologie

L'invention du naturel : les sciences et la fabrication du féminin et du masculin - Gardey, Delphine; Löwy, Ilana.. (Histoire des sciences, des techniques et de la médecine, 2000)
Comprendre ce que sont les hommes et les femmes, penser la différence entre les sexes a constitué et constitue encore un objet d'investigation et un enjeu politique et social de premier ordre. Des sciences d'hier à celles d'aujourd'hui, des discours et des pratiques médicales aux plus récentes sciences humaines, les auteurs de cet ouvrage révèlent la fragilité des évidences dites sur la nature ou le corps des femmes et des hommes, et insistent sur la force des arrangements et organisations du social qui ont pu en découler. Plus qu'une enquête descriptive sur les états variables des représentations proposées par les sciences, il s'agit d'analyser comment les scientifiques " en société " élaborent les critères de différenciation entre les sexes, contribuant à faire endosser à la nature certaines formes de domination. Convié à découvrir, en France et à l'étranger, l'histoire récente de ces nouveaux terrains d'enquête, le lecteur est aussi invité à méditer sur les effets de longue durée d'une modernité occidentale instaurée sous le signe de l'altérité entre raison et nature, hommes et femmes.
Keywords: approches et analyses; cours; discipline; discours dominant; essentialisation; genre; histoire et politique; identité sexuelle; naturalisation; premier cycle; production des savoirs; rapports sociaux de sexe; sciences; sciences humaines; sciences sociales; sex3383; sexe/genre; sociologie; systèmes d'oppressions; thématiques; épistémologies féministes

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Between men--between women, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Au sujet des corps, des techniques et des féminismes dans L'invention du naturel: les sciences et la fabrication du féminin et du masculin - Oudshoorn, Nelly (L'invention du naturel: les sciences et la fabrication du féminin et du masculin, 2000)
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; cours; discipline; essentialisme; europe; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques